The influence of English phonemic awareness to reading comprehension: A study on Indonesian EFL learners - Listyarini, Almaviana Ayu; Lintangsari, Alies Poetri; Emaliana, Ive (JEES (Journal of English Educators Society), 2022)
Phonemic Awareness has been reported to be one of the predictors to reading comprehension in English as a first language. However, it also comprises the second language reading comprehension. Various studies have reported the effects of English phonemic awareness to reading comprehension in English as a second or foreign language, but less similar research has been reported involving Indonesian EFL learners. Indonesia and English share different phonemes that affect learners' comprehension on English. This study aims to investigate the correlation between EFL learners’ phonemic awareness and reading comprehension. The subjects selected were 100 students from the 3rd semester majoring in English Language Education Program, in one of Indonesian university. There are two test obtained during this research, the first is phonemic identification test in order to measure the level of phonemic awareness, and the second is reading comprehension test to measure students’ reading comprehension skill. Simple linear regression was applied to validate the influence of English Phonemic Awareness to English Reading Comprehension. The result revealed that the correlation coefficient (r) value between the two variables shows .352 degrees with the significance level .000, while the coefficient of determination (r2) shows . HIGHLIGHTS: The importance of phonemic awareness in English reading comprehension The ability to identify English phoneme in isolation supports learners to link its letter sound which help them to develop their recognition on alphabetic code. Phonemic identification contributes to phoneme segmenting and blending knowledge that further support learners in word recognition and processing acquisition as the components of reading comprehension skill.